2003
DOI: 10.1677/joe.0.1760205
|View full text |Cite
|
Sign up to set email alerts
|

Insulin restores GH responsiveness during lactation-induced negative energy balance in dairy cattle: effects on expression of IGF-I and GH receptor 1A

Abstract: Early lactation in dairy cattle is a period of severe negative energy balance (NEB) characterized by reduced blood glucose and insulin concentrations and elevated blood GH concentrations. The liver is refractory to GH during NEB and this uncoupling of the GH-IGF axis results in diminished plasma concentrations of IGF-I. Our objectives were to examine the effects of insulin administration during the immediate postpartum period on plasma IGF-I and GH concentrations and to examine the hepatic expression of total … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
201
2
19

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 254 publications
(238 citation statements)
references
References 67 publications
16
201
2
19
Order By: Relevance
“…Accordingly, Vieira et al (2013) reported that dairy cows in adequate nutritional status receiving jugular glucose infusion (3 h at a rate of 0.5 g/kg of BW) had greater circulating insulin concentrations and reduced hepatic mRNA expression of P 4 catabolic enzymes CYP2C19 and CYP3A4 compared with cohorts receiving saline infusion. Butler et al (2003) observed that hepatic clearance of P 4 is reduced linearly after increasing amounts of insulin infusion. Therefore, it is possible that there is a minimum amount of insulin required to reduce the hepatic clearance of P 4 .…”
Section: Discussionmentioning
confidence: 96%
“…Accordingly, Vieira et al (2013) reported that dairy cows in adequate nutritional status receiving jugular glucose infusion (3 h at a rate of 0.5 g/kg of BW) had greater circulating insulin concentrations and reduced hepatic mRNA expression of P 4 catabolic enzymes CYP2C19 and CYP3A4 compared with cohorts receiving saline infusion. Butler et al (2003) observed that hepatic clearance of P 4 is reduced linearly after increasing amounts of insulin infusion. Therefore, it is possible that there is a minimum amount of insulin required to reduce the hepatic clearance of P 4 .…”
Section: Discussionmentioning
confidence: 96%
“…Plasma NEFA and BHBA levels are recognized as indicators for body fat mobilization and NEB in dairy cattle in early lactation [22,48,55,57]. Decreased plasma glucose and insulin levels have been associated with NEB [12, 13, 57, 58] and increase as cows progress towards a more positive EB [59].…”
Section: Effect Of Lipogenic and Glycogenic Nutrients On Blood Metabomentioning
confidence: 99%
“…Secondly, research on the relation between glycogenic nutrient addition and EB and reproductive parameters is desirable since studies on this subject are still scarce. Some suggestions can be made since glucose and insulin are increased after feeding extra glycogenic nutrients and are suggested as positive metabolic signals to the reproductive axis [11,13,19,57,118,135]. Plasma NEFA and BHBA levels are increased after feeding extra lipogenic nutrients and associated with decreased reproductive performance and anestrous [9,65,[136][137][138].…”
Section: Effect Of Lipogenic and Glycogenic Nutrients On Reproductivementioning
confidence: 99%
“…However, the lack of correlation between GHR and IGF-I mRNA in the granulosa cells of large follicles has also been suggested in cattle (Rhoads et al, 2008), since there is no clear evidence that GH controls IGF-I secretion in the follicle (Lucy, 2000). Despite that, evidence indicates that IGFBP-2 to 26 (IGF-binding protein) are expressed in the ovine follicle (Hastie and Haresign, 2010) and that insulin levels can modulate free IGF-I availability through the modulation of IGFBP levels (Butler et al, 2003). In this way, although IGF-I mRNA expression was not different among groups, its intrafollicular availability could have been altered due to the effects of insulin on IGFBP.…”
Section: Discussionmentioning
confidence: 99%
“…This happens -E-mail: augusto.schneider@live.com because insulin concentration is reduced, and so is GHR expression in the liver (Butler et al, 2003). However, the infusion of insulin during negative energy balance is able to restore the coupling of the GH-IGF-I axis and increase circulating IGF-I concentration (Butler et al, 2003).…”
Section: Introductionmentioning
confidence: 99%